Guide to antimicrobial use in animals (Blackwell Pub., 2008)
The first book to offer practical guidelines on the prudent and rational use of antimicrobials in animals. The earlier chapters cover issue such as human health risk and the problems of resistance to antimicrobial drugs. The later chapter are specifically dedicated to particular groups of animals, and include tables of the drugs of choice to be used to preserve the efficacy of clinically important antimicrobials.